CircNF1 modulates the progression and immune evasion of esophageal squamous cell carcinoma through dual regulation of PD-L1 - Chang Wang; Chenxi Ju; Dan Du; Peiyu Zhu; Jie Yin; Jinlin Jia; Xue Wang; Xinyu Xu; Li Zhao; Junhu Wan; Ting Sun; Lijun Yang; et al. (Cellular & Molecular Biology Letters)
Abstract Background Tumor immune escape is a pivotal gateway for esophageal squamous cell carcinoma (ESCC) development. Immune checkpoint-blocking therapies, represented by programmed cell death receptor-1/ligand 1 (PD-1/PD-L1) inhibitors, have achieved remarkable breakthroughs in ESCC treatment. However, not all patients with ESCC receive satisfactory clinical benefit. Therefore, identifying novel biomarkers for predicting the efficacy of immunotherapy in ESCC is of great importance. Methods CircNF1 was screened from the circRNAs microarray, and its expression was measured by droplet digital polymerase chain reaction (ddPCR) and quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) assays in ESCC tissues and serum. Functional experiments were conducted to demonstrate the role of circNF1 in ESCC proliferation, metastasis, and tumor evasion. High-throughput RNA sequencing, chromatin immunoprecipitation (ChIP), co-immunoprecipitation (co-IP), and chromatin isolation by RNA purification-mass spectrometry (ChIRP-MS) were performed to clarify the underlying mechanisms of circNF1-mediated tumor progression. Results The upregulation of circNF1 was closely associated with the response of anti-PD-L1 immunotherapy. Functionally, circNF1 promoted ESCC cell malignant phenotypes and regulated CD8+ T-cell-mediated antitumor immunity. Mechanistically, circNF1 drove the IL-6-induced oncogenic activation of the JAK–STAT3 pathway, which stimulated p-STAT3 binding of the promoter regions of PD-L1. Furthermore, circNF1 physically interacted with annexin A1 (ANXA1), blocking the ANXA1 deubiquitination induced by ubiquitin-specific protease 7 (USP7), resulting in increased interaction between USP7 and PD-L1 and augmented PD-L1 stability. Conclusions Our findings provide novel insights into the specific regulatory mechanism of PD-L1 in ESCC cells, which offer a new strategy for synergizing with anti-PD-L1 therapy.